Management and Utilization Strategies of Educational Management Information Systems to Enhance Students' Academic Performance - Pramono, Susatyo Adhi; Hanif, Muh.; Kraugusteeliana, Kraugusteeliana (Indo-MathEdu Intellectuals Journal, 2024)
Conventional educational management systems often face limitations in handling student data, curriculum, and other academic processes, leading to difficulties in effectively monitoring and enhancing students' academic performance. With the rapid advancement of information technology, the use of management information systems in educational contexts has become increasingly crucial. This research aims to examine the management and utilization strategies of management information systems in enhancing students' academic performance. The methodology employed in this research is a literature review using a qualitative approach and descriptive analysis. Descriptive analysis is utilized to present characteristics, patterns, and trends emerging from data obtained from articles published on Google Scholar between 2007 and 2024. Theme identification is one of the research data analysis techniques. The main themes in the article were identified, focussing on aspects such as information systems, education management, and student academic performance. The study results indicate that the utilization of Management Information Systems (MIS) has demonstrated a significant role in enhancing efficiency and effectiveness across various fields, including education. In the educational context, the management of MIS can be a key factor in improving students' academic performance